Are antivirals effective in treating Bell's palsy?. Issue 6 (June 2018) - Beard, Mark J.; Hyde, Nicola
Abstract : EVIDENCE‐BASED ANSWER : Antivirals alone are no better than placebo for the treatment of Bell's palsy. Antivirals in addition to corticosteroids result in a modest improvement in full recovery rates compared with corticosteroids alone (SOR: B, meta‐analysis of lower quality RCTs). Clinical practice guidelines recommend offering antivirals only in conjunction with oral steroids to appropriate patients with Bell's palsy (SOR: C, clinical guidelines).